2003
DOI: 10.1089/109065703322783743
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Mutation in the ARSB Gene That Is Frequent Among Brazilian MPSVI Patients

Abstract: Mucopolysaccharidosis type VI, or Maroteaux-Lamy syndrome, is an autosomal recessive disease caused by the deficiency of arylsulfatase B (ARSB; N-acetyl-galactosamine-4-sulfatase, E.C.3.1.6.12), which is involved in the stepwise degradation of dermatan sulfate and chondroitin sulfate. The deficiency of this enzyme causes storage in the lysozomes and excretion in the urine of partially degraded dermatan sulfate. Twenty patients with MPSVI were analyzed, including 2 siblings. Genomic DNA from patients was extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…The 4 deceased Monte Santo patients, 2 males and 2 females, were between 7 and 19 years of age at their death and, prior to death, they had also been shown to be homozygous for the p.H178L mutation ( table 1 ). By comparison, c.1533del23 has been reported to be the most common MPS VI mutation elsewhere in Brazil [22,23] . In addition to the 13 genomically confirmed cases, family members identified another 33 deceased persons with the characteristic MPS VI phenotype who had died at between 1 and 24 years of age ( table 2 ; fig.…”
Section: Resultsmentioning
confidence: 88%
“…The 4 deceased Monte Santo patients, 2 males and 2 females, were between 7 and 19 years of age at their death and, prior to death, they had also been shown to be homozygous for the p.H178L mutation ( table 1 ). By comparison, c.1533del23 has been reported to be the most common MPS VI mutation elsewhere in Brazil [22,23] . In addition to the 13 genomically confirmed cases, family members identified another 33 deceased persons with the characteristic MPS VI phenotype who had died at between 1 and 24 years of age ( table 2 ; fig.…”
Section: Resultsmentioning
confidence: 88%
“…Moreover, Brazil had a higher birth prevalence of MPS VI (0.31) than most European countries but similar to Estonia, Tunisia, and West Australia [28]. There is a common mutation, 1533del23, among Brazilian MPS VI patients found in 23.1% of alleles, which also occurs in Portuguese MPS VI patients [111116] that could reflect the high incidence of Brazilian MPS VI.…”
Section: Discussionmentioning
confidence: 99%
“…Nonsense mutations and small insertions or deletions comprise the remainder, with seven mutations each. In 2003 and 2005, Petry et al described a common mutation, 1533del23, among Brazilian MPS VI patients found in 6/26 alleles (23.1%), which also occurs in Portuguese MPS VI patients, although the frequency is unknown [111116]. In 2007, Karageorgos et al reported a cohort of 105 MPS VI patients from 15 countries, but primarily from Australia, Europe, North America, and South America that represented more than 10% of the world’s MPS VI patients [113].…”
Section: Methodsmentioning
confidence: 99%
“…The panel of mutations detected so far is fairly heterogeneous (Karageorgos et al , 2007), with a low relative frequency of each mutation. Only in Portugal and in Brazil have relatively common mutations been identified (Petry et al , 2003, 2005). A correlation between urinary GAG excretion and the clinical phenotype has now been established (Swiedler et al , 2005), but there is no well-established correlation yet with the genotype of the affected individuals (Litjens et al , 1996).…”
Section: Biochemical and Genetic Aspectsmentioning
confidence: 99%